Criteria of Career Success Among Chinese Employees: Developing a Multidimensional Scale With Qualitative and Quantitative Approaches. (May 2013) - Zhou, Wenxia; Sun, Jianmin; Guan, Yanjun; Li, Yuhui; Pan, Jingzhou
The current research aimed to develop a multidimensional measure on the criteria of career success in a Chinese context. Items on the criteria of career success were obtained using a qualitative approach among 30 Chinese employees; exploratory factor analysis was conducted to select items and determine the factor structure among a new sample of Chinese employees ( N = 550); confirmatory factor analysis was conducted among another sample of Chinese employees ( N = 199). The results showed that Chinese employees regard intrinsic fulfillment, external compensation, and work–life balance as the major components of career success. The developed scale showed good reliability and structure validity. Implications for future research on career success were discussed.